CORRELATION BETWEEN DEPRESSION AND CHRONIC LOW BACK PAIN (CLBP) AMONG ADULT INDIVIDUALS - Imran Raza; Iram Bokhari; Sana Akbar Qazi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Patients who have chronic low back pain (CLBP) often visit medical clinics to address this common problem. Approximately 577 million people worldwide, or 7.5% of the total population, suffered from low back pain in 2017. Depression is a mental health concern, despite the fact that CLBP is a physical illness. Back pain is widespread from puberty to elderly, and it becomes more likely to occur as people become older. Pain that persists for longer than 12 weeks is referred to as chronic pain. Between 25% and 76% of older individuals living in communities experience chronic pain, including CLBP, which is the second most prevalent cause of disability across all adult age groups. Objective: To examine the correlation between depression and CLBP among adult individuals. Study design:Analytical cross sectional analysis Place and Duration: This study was conducted in Jinnah Postgraduate Medical Center Karachi from December 2022 to December 2023 Methodology: Using a non-probability convenience sampling technique, 180 people who had been suffering from persistent low back pain for three months or more and were at least 20 years of age were included in the study. The PHQ-9 questionnaire was used in the study to measure depression symptoms, and the Numeric Rating Scale (NRS) and Wong Baker Faces Pain Rating Scale were used to measure pain severity. Results: There were a total of 180 patients involved in this research. The average age in this study was 61 years for patients who were diagnosed with moderate CLBP and for patients with severe pain, the average age was 64 years. There were 100 individuals who had moderate low back pain, 30 individuals who had severe low back pain, and 50 individuals who had mild low back pain. There were a total of 88 males and 92 females in this study. Conclusion: Since higher pain scores are correlated with higher depression, screening for depression is essential in the treatment of CLBP.